Reviewing 15 years of experience with sirolimus. Issue 1 (December 2015) - Tedesco Silva, Helio; Rosso Felipe, Claudia; Medina Pestana, Jose
Abstract Here, we review 15 years of clinical use of sirolimus in our transplant center, in context with the developing immunosuppressive strategies use worldwide. The majority of studies were conducted in de novo kidney transplant recipients, using sirolimus (SRL) in combination with calcineurin inhibitors (CNIs). We also explored steroid (ST) or CNI-sparing therapies, including CNI minimization, elimination, or conversion strategies in combination with mycophenolate (MMF/MPS). Pooled long-term outcomes were comparable with those obtained with CNI and antimetabolite combination. Surprisingly, there are still several areas that need further investigation to improve the risk/benefit profile of SRL in kidney transplantation, including pharmacokinetic/pharmacodynamic drug-to-drug interaction with cyclosporine (CsA) or tacrolimus (TAC), mechanisms of SRL-associated adverse reactions and combinations with other drugs such as belatacept and once-daily TAC, possibly leading to improved long-term adherence. These studies, along with others investigating the benefits of SRL associated lower viral infections and malignancies, are essential as we do not expect the introduction of new immunosuppressive drugs in the near future.